Hydrocarbon Potential Assessment for Dokan and Gulneri Formations (Upper Cretaceous) in K-130 Well Kirkuk Oil Field, Kurdistan, North of Iraq - Farraj, Razawa H. (Sulaimani Journal for Pure and Applied Sciences, 2017)
Eight rock samples from the Dokan and Gulneri formations in one subsurface section of Kirkuk-130 Well in Northern Iraq were chosen to be studied optically and analytically to determine the source- rock properties of the both rock units. The studied samples showed richness in amorphous organic matter with generally low percentages for other organic matter components. Three palynofacies were distinguished representing proximal suboxic-anoxic shelf and shelf- to – basin transition for the Dokan Formation, whereas a distal suboxic-anoxic basin appeared to be the paleodepositional environment for the Gulneri Formation.The Dokan Formation appears to be poor to fair, whereas the Gulneri Formation showed very good to excellent richness in organic matter as measured from total organic carbon (TOC) contents. The Rock- Eval Pyrolysis data for the studied formations showed that the quality of organic matter in the Dokan Formation is mostly type II/III kerogen, whereas in the Gulneri Formation it is mostly type I kerogen. Thermal maturity indicators, as observed from pyrolysis parameters, indicate an immature state for both studied formations. Accordingly, it is concluded that the Dokan and Gulneri formations did not contribute to generating the accumulated oil in the Kirkuk Field.
Keywords: Dokan; Gulneri; Kirkuk Oil Field; Rock Eval Pyrolysis Kurdistan